Enhancing performance of recycled aggregate concrete with supplementary cementitious materials - Abba Fatiha; Ezziane Karim; Adjoudj Mhamed; Abed Farid (Cleaner Materials)
The substitution of natural coarse aggregates (NCA) by recycled coarse aggregates (RCA) is part of the environmental approach aimed at reducing waste and preserve natural resources. Unfortunately, RCA is of poor quality due to the presence of old mortar attached to its surface. It is characterized by its low density, high absorption, low rigidity and a poor quality interfacial transition zone (ITZ) which results in a lower quality concrete. This experimental study aims to introduce together with RCA aggregates supplementary cementitious materials (SCM) in order to reduce the decrease in mechanical performance, durability and microstructure of concrete. In a concrete based on RCA aggregates, ordinary cement was replaced with 20% natural pozzolan (NP), 10% limestone powder (LP), 20% ground granulated blast furnace slag (GGBFS) or 10% fumed silica (SF). Concrete was studied in terms of workability, superplasticizer requirements, mechanical strength, water absorption and microstructure. The results reveal that SCM significantly improves the performance of RAC concrete by promoting filling effects, nucleation, pozzolanic reactions and hydraulic activity. In the long term, RAC concrete has a 12% lower strength than OAC concrete. This decrease is reduced to only 3% when using LP and even results in 9% and 28% higher strengths when using GGBFS or SF. Similarly, an improvement in structural porosity up to 28% is observed, which led to a significant reduction in shrinkage strain, ranging from 20% to 44%.